PENANAMAN NILAI–NILAI ISLAM BERUPA INTEGRASI AL-QURAN DALAM PENGAJARAN ILMU KAUNIYAH MELALUI RPP - Amalia Nurjannah (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2016)
The aim of planting the islamic values is to realize generation with noble caracter that has strong faith and knowledge. Integrating Islam with the studies in kauniyah is an idea that is based on the assumption that the development of the studies in kauniyah in the Islamic context is a necessity for the continuation of human civilization harmony in the future. Integration of Al-Quran in the teaching of the studies in kauniyah through the lesson plan is one way to implanting the islamic values in students . The way that is done is also prepared lesson plan of the studies in kauniyah developed by integrating the verses of the Al-Quran that are relevant to the material being taught.